2015
DOI: 10.2174/1566524015666150330142807
|View full text |Cite
|
Sign up to set email alerts
|

Specific Roles of NMDA Receptor Subunits in Mental Disorders

Abstract: N-methyl-D-aspartate (NMDA) receptor plays important roles in learning and memory. NMDA receptors are a tetramer that consists of two glycine-binding subunits GluN1, two glutamate-binding subunits (i.e., GluN2A, GluN2B, GluN2C, and GluN2D), a combination of a GluN2 subunit and glycine-binding GluN3 subunit (i.e., GluN3A or GluN3B), or two GluN3 subunits. Recent studies revealed that the specific expression and distribution of each subunit are deeply involved in neural excitability, plasticity, and synaptic def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 155 publications
(156 reference statements)
1
19
0
Order By: Relevance
“…Furthermore, genetic variation in SYNJ2, another gene identified in our epigenome-wide analyses, has been linked to corpus callosum abnormalities (Edwards et al, 2014), which are robustly associated with maltreatment (McCrory et al, 2012). Other psychopathology-relevant genes included glutamate and GABA receptors (GRIND2D, GABBR1), which play a key role in excitatory and inhibitory neurotransmission, respectively (Kumar et al, , Yamamoto et al, 2015. Prospective studies will be needed to explicitly test whether the DNAm sites identified in the present study associate with psychopathological outcomes and, if so, whether they may mediate the influence of abuse and neglect on later mental health.…”
Section: The Identified Dna Methylation Markers Support a Molecular Lmentioning
confidence: 94%
“…Furthermore, genetic variation in SYNJ2, another gene identified in our epigenome-wide analyses, has been linked to corpus callosum abnormalities (Edwards et al, 2014), which are robustly associated with maltreatment (McCrory et al, 2012). Other psychopathology-relevant genes included glutamate and GABA receptors (GRIND2D, GABBR1), which play a key role in excitatory and inhibitory neurotransmission, respectively (Kumar et al, , Yamamoto et al, 2015. Prospective studies will be needed to explicitly test whether the DNAm sites identified in the present study associate with psychopathological outcomes and, if so, whether they may mediate the influence of abuse and neglect on later mental health.…”
Section: The Identified Dna Methylation Markers Support a Molecular Lmentioning
confidence: 94%
“…More differentiated cells expressing AMPAR and NMDAR subunits also expressed CAMK2A , allowing them to be identified using a CAMK2A::GFP reporter gene. This approach allowed the isolation of highly differentiated and synaptically active human patterned induced neurons (hpiNs), underscoring the potential utility of this approach for modeling diseases associated with glutamate receptor dysfunction, including schizophrenia, epilepsy, and autism ( Yamamoto et al, 2015 ; Yuan et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, McOmish et al [25] demonstrated that environmental enrichment rescued loss of muscarinic cholinergic receptors in the neocortex and hippocampus of the PLC-β 1 knockout model in the mouse, but there were limited effects of enrichment on behavioral outcomes in this model, with no effect of environmental enrichment on prepulse inhibition, exploratory behavior, or cognitive deficits in the Morris water maze. Koseki et al [26] found that environmental enrichment potentiated the hyperlocomotor behavioral response to acute treatment with phencyclidine, an antagonist to glutamatergic NMDA receptors which has relevance to the NMDA receptor hypofunction known to exist in schizophrenia [51]. Environmental enrichment also prevented chronic phencyclidine treatment-induced impairments of social behavior and recognition memory in the social interaction and novel object recognition tests, but neither sensitization nor associative effects of phencyclidine were analyzed in this study.…”
Section: Discussionmentioning
confidence: 52%